Qualitative and Quantitative Screening of Phytochemicals in Polar and Non Polar Solvent Extracts of Stem Bark and Leaves of Saraca Indica - Gogate, Shweta; Mathur, Rahul; Raghuvanshi, Arpit; Yadav, Ashutosh kumar; Dhurve, Deepak; Sen, Dheeraj Kumar; Raj, Divya; Rathi, Jagdish (Asian Journal of Pharmaceutical Research and Development, 2022)
The present work can serve as a valuable source of information and provide appropriate standards to establish the quality of this plant material in future prospective study. From the results it is evident that the bark and leaves of Saraca indica contain a significant amount of phytochemicals viz. alkaloid, flavonoids, phenolic, saponins and tannin. The bark of Saraca indica contained relativelely higher amounts of phytochemicals than leaves. The comparative analysis of phytochemicals viz. total alkaloids, flavonoids, phenols, saponins and tannins in different solvent extracts from bark and leaves of Saraca indica